Intrahepatic Cholangiocarcinoma in Bitches of the Springer Spaniel Breed - Rincón, Gennyffer; Albarracín, Javier Hernado; Duarte, Luz Zoraya (Spei Domus, 2014)
Cholangiocarcinoma or cgc is a intrahepatic primary tumor characterized by its generating of nonspecific signs that are difficult to diagnose. Ultrasound-guided cytology or exploratory laparotomy help analyze it, with the drawback being that in most cases the growth of the tumor is compromising approximately 60% of the liver tissue. Histopathological diagnosis allows the identification and prognosis of the disease’s progress. Clinical findings did not indicate liver failure, but in this case they did show hypoproteinemia and abnormalities in liver silhouette ultrasounds.